Distance Learning Course of Written Communication in Teaching German as Foreign Language - Y. E. Myuller (Научный диалог)
The author’s project is presented - distance learning course on the Moodle platform on German as a foreign language in higher educational institution (University Duisburg-Essen, Germany), the aspect of “written communication.” The research urgency is caused by the fact that the growth of academic mobility in higher education causes the need to intensify the teaching of foreign languages, at the same time, the development of modern communications technology expands the possibilities of knowledge transfer and competence forming. The experience of the e-learning course is described, approaches to learning and their refraction in the structure of the course are presented: competence, communicative activity, intercultural. A thematic plan of the course, including the types of written texts, provided by “the common European framework of reference for languages” is provided. Special attention is paid to the organization of the thematic units of the course in accordance with the concept of “backward planning.” Criteria for intermediate and final assessment are identified. Practical significance is determined by the fact that standards of provision of learning material can be used to create distance and blended courses on other aspects of teaching foreign languages in higher professional education of the Russian Federation.